Photoring: Definition, implementation and comparison of two different backend architectures (2017)
Traditional tools for the the exploration and visualization of digital photo collections do not provide a usable easy-to-use interface for users to interact with. In addition, these tools usually do not convey all possible characteristics that photos in the collection have ( e.g. Date, Author, Location). As collections increase in size and characteristics, a new challenge appears: representing the collection in an efficient persistence data model. To address the first two problems we present Photoring, an alternative tool for the navigation, exploration and visualization of large photo collections. It offers a simple easy-to-use interface and it can also fully convey all possible characteristics of a collection. Finally, we implemented the data model for a particular collection in two different database schemas: mySQL and MongoDB. We then compared both implementations in terms of suitableness to the problem, ease of implementation and efficiency